Review on liquid chromatography coupled with mass spectrometry applied to food toxicological analysis (Research, Society and Development, 2021)
High performance liquid chromatography (HPLC) coupled with mass spectrometry (MS) is one of the most important analytical techniques used in the determination of non-volatile or thermally unstable compounds. The combination of both unites the excellence of the separation of the analyte of interest in the matrix through the high performance liquid chromatography technique, together with the mass spectrometry technique that confirms the chemical identification. Among the available alternatives, mass spectrometry is the one that best provides the necessary structural information. The coupling between these two techniques gives rise to a robust, versatile and great potential analytical tool in the qualitative and quantitative analysis in food toxicology. This article presents a literature review that aims to present the fundamentals of the application of the coupling of Liquid Chromatography and Mass Spectrometry in the area of food analysis.